A study to evaluate the performance of black South African urban infants on the Bayley Scales of Infant Development III - Rademeyer, Vanessa Kathleen May (My University, 2012)
South Africa (SA) needs a suitable tool to evaluate child development as no such tool exists at present. Well known standardised tests are designed in First World Countries but pose problems when used on different populations. The Bayley Scales of Infant Development, a tool designed and normed in the United States of America (USA) is considered to be the gold standard in infant assessment. The revised and updated, 3rd edition was published in 2006. No studies have been done on its use on populations other than the USA. The USA and SA populations are very different and therefore may perform differently on developmental tests since previous research has shown that African infants perform better than USA infants. The main aim of this study was to use the Bayley Scales of Infant and Toddler Development III (Bayley-III) to evaluate the performance of a cohort of black urban African infants in South Africa, in an effort to determine whether it is a suitable tool for use on this population. The Hypothesis was that SA and USA children perform similarly on the test. Other objectives included assessing whether gender or anthropometric indicators influence performance. The revised 3rd edition of the Bayley Scales of Infant Development (Bayley-III) was used to assess the performance of 122 black African infants at several urban clinics in Gauteng, South Africa. The sample consisted of infants falling into four age categories; 3, 6, 9 and 12 months. SA scores were compared to USA norms. Scores were compared across age groups, subtests and sex. Height, weight and head circumference was also measured, converted into z-scores and correlated with test scores. Overall the SA mean score was 103.4, which is statistically significantly higher (p=0.0007) than the USA mean of 100.For subtests, the mean score was 99.7 for the cognitive, 106.8 for the language and 103.5 for the motor subtests as opposed to 100 for the USA. Therefore the results of this study showed that SA scores were statistically significantly higher than the USA norms. Gender differences in scores for specific subtests were found, indicating that girls and boys perform differently developmentally at different ages. However this analysis was at subgroup level with individually small numbers and further research is required to investigate this. Anthropometric indicators such as height, weight and head circumference were found to have no significant association with scores on the test, indicating that growth had no effect on development in this population Although the overall SA mean (103. 4) was statistically significantly higher than the USA mean (100), clinically the difference is small when one considers the variability of development. Developmental milestones can be reached within a range of months and can vary considerably. The Bayley-III is therefore a suitable tool to use on this population. More research is recommended to assess a larger more diverse group, including all age groups for which the Bayley-III caters, as well as on all population groups in SA.
Keywords: Child Development